Methods of Evaluation of Output Signals from Resonance Accelerometers - Stanislav ĎAĎO (Sensors & Transducers, 2014)
In this paper two novel modifications of Weighted Least Square Method (WLSM) of frequency estimation suitable for evaluation of rapid changes of frequency occurring in resonance sensors are introduced and experimentally verified. The efficiency of the WLSM methods is compared to the nano-counting approach representing a substantial improvement of well-known start-stop methods of frequency measurement and estimation.